Study Antibacterial Activity of Crude Capparis spinosa L. Extracts Against Helicobacter pylori Infection and Determine Their Bioactive Compounds - Al-Khafagi, Manar F. Jassim; Mohammed, Dina Yousif (Iraqi Journal of Science, 2023)
The antibacterial activity of Capparis spinosa L. extracts obtained from Baghdad was evaluated against six clinical bacteria isolates of Helicobacter pylori. The results presented in this work demonstrated that the leaves extract showed a significant effect against bacteria as compared to the root and fruit extracts at 100 mg/ml concentration, with inhibition zone ranging from 12.0 to 30.7 mm in each bacteria strain. The end results of GC-MS analysis indicated that the ethanol extracts of caper have a lot of active chemical compounds, including twenty-five, eighty-two and sixty-eight phytoconstituent compounds, that are distinguished in the extracts of roots, leaves and fruits with C. spinosa L. respectively. In addition, the high area % revealed in each extracts were: 1-methyl-pyrrolidine-2-carboxylic acid 35.77%, prolin, N-methyl-, butyl ester 12, 63% and (23S)-ethylcholest-5-en-3.beta.-ol 19.12% respectively.